Effect of Short-Term Rotifer Enrichment With Marine Phospholipids on Growth, Survival, and Composition of Meager (Argyrosomus regius) Larvae - Ghaderpour, Sirwe; Estevez, Alicia (Frontiers in Marine Science, 2020)
Larval rearing and ongrowing of meagre have advanced a lot during the last years and nowadays this species is one of the most important in Mediterranean aquaculture. However, larval nutrition still has unanswered issues to address, specifically in regard to live prey enrichment and fatty acid composition. In this study, an experimental trial for larval rearing of meagre (Argyrosomus regius) using different products for rotifer enrichment (Multigain, Red Pepper and concentrated microalgae) with and without phospholipids (PL), and with a different fatty acid composition, especially regarding DHA, have been used to assess the growth and survival of the larvae and check the effect of PLs in relation to growth. Lipid class composition was the same among the larvae whereas % DHA was always higher in larvae fed Multigain and Red Pepper enriched rotifers. The dominant fatty acids in the PL of the larvae and PL of the diets were well correlated and the results suggested a close relationship between the composition of dominant PL fatty acids in the rotifer and in the larvae, especially in the case of DHA and 16:0 that show a high correlation